The poetic criticism discourse in master theses in bahdinani region: two master theses as samples - Abdulrahman, Yahman; Shuan, Ibrahim (Humanities Journal of University of Zakho, 2023)
Literary criticism deals with searching and analyzing the creative text in order to show the characteristics, value and the beauty of a literary text. To achieve this goal, critics use critical methods. Each critical method consists of a number of terms and critical procedures. Critics and the rhetorics of criticizing critical works consider the level of criticism; as how academic critics deal with criticism. The important point for them is how is criticism? Is it accurate in terms of goals, body and critical practicing. This study is entitled (The Poetic Criticism Discourse in Master Theses in Bahdinani Region: Two Master Theses as Samples). This research tries to show the level of poetic criticism discourse in academic theses in Bahdinan Region. The results show that critical awareness is clear in the theses that adopted a specific method more than in the ones that does not use any critical method.